Pertanggungjawaban Negara Dalam Kegiatan Komersiil Ruang Angkasa Yang Dilakukan Oleh Perusahaan Swasta - Sri Wartini (Fakultas Hukum Universitas Islam Indonesia, 2005)
Commercial space activWes conducted by private company may raise legal problems which relate to state responsibility. State Responsibility can be embodied in the national regulation, national policies and effective control of commercial space activities by the government, such as permit system with specific and private company to participate on the commercial space activities. Therefore, the company is able to fulfil its responsibility and liability if its activities cause disadvantage to the third parties.